COVID-19 labour market shocks and their inequality implications for financial wellbeing - Ferdi Botha; John P. de New; Sonja C. de New; David C. Ribar; Nicolás Salamanca (Global Labor Organization (GLO), 2020)
Using an online survey of Australian residents, we elicit the potential impacts of COVID-19 related labour market shocks on a validated measure of financial wellbeing. Experiencing a reduction in hours and earnings, entering into unemployment or having to file for unemployment benefits during the pandemic are strongly and significantly associated with decreases in financial wellbeing of 29% or 18 points on the financial wellbeing scale of 0-100, despite various government measures to reduce such effects. Unconditional quantile regression analyses indicate that the negative COVID-19 labour market effects are felt the most by people in the lowest percentiles of the financial wellbeing distribution. Counterfactual distribution regressions indicate a shifting of the financial wellbeing distribution leftwards brought on by those suffering any of the above-mentioned labour market shocks, indicating potential significant increases in financial wellbeing disadvantage and inequality.
Keywords: D14; D39; J65; G51; D63; 330; Financial wellbeing; COVID-19; unemployment; earnings reduction; inequality